2009
DOI: 10.1186/1423-0127-16-89
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the fusion peptide-like domain of hepatitis C virus E1 glycoprotein: involvement in cell fusion and virus entry

Abstract: BackgroundEnvelope (E) glycoprotein E2 of the hepatitis C virus (HCV) mediates binding of the virus to target cell receptors. Nevertheless, the precise role of E1 in viral entry remains elusive.MethodsTo understand the involvement of the fusion peptide-like domain positioned at residues 264 to 290 within envelope glycoprotein E1 in HCV infection, mutants with Ala and Asn substitutions for residues conserved between HCV and E proteins of flaviviruses or the fusion proteins of paramyxoviruses were constructed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…It has been proposed that a conserved hydrophobic sequence, CSALYVGDLC (residues 272 to 281), in E1, which was not included in the structural analysis of nE1, may represent a truncated class II fusion peptide (27). The role of this sequence in virus entry and membrane fusion was supported by data from several studies (27)(28)(29)(30)(31)(32). The potential role of this putative fusion peptide in E1 in other aspects of the HCV life cycle has not been explored.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…It has been proposed that a conserved hydrophobic sequence, CSALYVGDLC (residues 272 to 281), in E1, which was not included in the structural analysis of nE1, may represent a truncated class II fusion peptide (27). The role of this sequence in virus entry and membrane fusion was supported by data from several studies (27)(28)(29)(30)(31)(32). The potential role of this putative fusion peptide in E1 in other aspects of the HCV life cycle has not been explored.…”
mentioning
confidence: 62%
“…It was reported previously that a region (amino acid residues 272 to 285) ( Fig. 5A) in HCV E1 is a putative FP, which plays an important role in triggering the fusion of the viral envelope and endosomal membrane during the HCV entry process (27)(28)(29)(30)(31)(32). We first examined the role of FP using lentivirus-based HCV pseudotype particles (HCVpp) that harbor the HCV envelope proteins E1 and E2 and mimic the HCV entry process (36,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation analysis of hydrophobic residues in the putative fusogenic region of E1 has revealed that only the F285A mutant abolished viral entry whereas other mutations did not affect or only partially inhibited viral entry (Drummer et al, 2007). Finally, it has been reported that specific residues between positions 264 and 290 within E1, but not the structure, are responsible for fusion (Li et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The model also shows that C272 from nE1 is very close to C281 in the putative fusion peptide of E1, suggesting a potential for interactions. However, Li et al (65) noted that it is unlikely that these two residues are disulfide linked, since E1/E2 from HCV pseudoparticles (HCVpp) with the mutations C272A and C281A did not migrate differently on reducing or nonreducing SDS-PAGE gels compared to wild-type E1/E2. It is unclear based on experimental data in the literature which, if any, disulfide linkages are formed between E1 and E2 within the heterodimer and in the higher-order structure.…”
Section: Figmentioning
confidence: 99%